Analysis of the related factors of atypical squamous cells of undetermined significance (ASC-US) in cervical cytology of post-menopausal women - Li, Bijun; Dong, Lichang; Wang, Chen; Li, Jia; Zhao, Xue; Dong, Mengting; Li, Huanrong; Ma, Xiaotong; Dong, Yalan; Wu, Ming; Yan, Ye; Fan, Aiping; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Atrophy of the reproductive tract mucosa caused by the decrease of estrogen may increase the detection rate of ASC-US in cervical cytology of post-menopausal women. In addition, other pathogenic infections and inflammation can change the cellular morphology and increase the detection rate of ASC-US. However, further studies are needed to elucidate whether the high detection rate of ASC-US in post-menopausal women leads to the high referral rate of colposcopy. Methods This retrospective study was conducted to document ASC-US in cervical cytology reports at the Department of Cytology at Gynecology and Obstetrics, Tianjin Medical University General Hospital between January 2006 and February 2021. We then analyzed 2,462 reports of women with ASC-US at the Cervical Lesions Department. A total of 499 patients with ASC-US and 151 cytology with NILM participants underwent vaginal microecology tests. Results The average reporting rate of ASC-US in cytology was 5.7%. The detection rate of ASC-US in women aged > 50 years (7.0%) was significantly higher than that in women aged ≤50 years (5.0%) (P<0.05). The CIN2+ detection rate was significantly lower in the post- (12.6%) than in pre-menopausal (20.5%) patients with ASC-US (P <0.05). The prevalence of abnormal reporting rate of vaginal microecology was significantly lower in the pre-menopausal group (56.2%) than that in the post-menopausal group (82.9%) (P<0.05). The prevalence of bacterial vaginosis (BV) (19.60%) was relatively high in the pre-menopausal group, but the abundance of bacteria-inhibiting flora (40.79%) was mainly an abnormality in the post-menopausal group. The vaginal microecological abnormality rate of the women with HR-HPV (-) of ASC-US was 66.22%, which was significantly higher than that of the HR-HPV (-) and the NILM group (52.32%; P<0.05). Discussion The detection rate of ASC-US in women aged > 50 years was higher than that ≤50 years, but the detection rate of CIN2+ was lower in the post-menopausal women with ASC-US. However, vaginal microecological abnormalities may increase the false-positive diagnosis rate of ASC-US. The vaginal microecological abnormalities of the menopausal women with ASC-US are mainly attributed to infectious diseases such as BV, and it mainly occurs in the post-menopausal women was bacteria-inhibiting flora. Therefore, to avoid the high referral rate for colposcopy, more attention should be paid to the detection of vaginal microecology.